2018
DOI: 10.1039/c8nr01550c
|View full text |Cite
|
Sign up to set email alerts
|

A nanoporous MXene film enables flexible supercapacitors with high energy storage

Abstract: MXene films are attractive for use in advanced supercapacitor electrodes on account of their ultrahigh density and pseudocapacitive charge storage mechanism in sulfuric acid. However, the self-restacking of MXene nanosheets severely affects their rate capability and mass loading. Herein, a free-standing and flexible modified nanoporous MXene film is fabricated by incorporating Fe(OH)3 nanoparticles with diameters of 3-5 nm into MXene films and then dissolving the Fe(OH)3 nanoparticles, followed by low calcinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
98
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(109 citation statements)
references
References 53 publications
5
98
0
1
Order By: Relevance
“…When areal capacitances as a function of MXene mass loading are plotted (Figure d and Figure S7 in the Supporting Information), an excellent linear relationship is presented at current density less than 30 mA cm −2 . To our knowledge, once MXene loading increases, the areal capacitance becomes very difficult to increase proportionately, as found in other reports . This demonstrates that our method is very effective to facilitate the ion diffusion and improve the electrochemical performance of flexible electrodes.…”
Section: Resultssupporting
confidence: 73%
“…When areal capacitances as a function of MXene mass loading are plotted (Figure d and Figure S7 in the Supporting Information), an excellent linear relationship is presented at current density less than 30 mA cm −2 . To our knowledge, once MXene loading increases, the areal capacitance becomes very difficult to increase proportionately, as found in other reports . This demonstrates that our method is very effective to facilitate the ion diffusion and improve the electrochemical performance of flexible electrodes.…”
Section: Resultssupporting
confidence: 73%
“…Nanoporous Mxene films were formed using Fe(OH) 3 nanoparticles, which were used in order to prevent re‐stacking of Mxenes ( Figure 20 ). [ 265 ] This approach facilitated the formation of highly interconnected nanopore channels, which promoted efficient ion transport. It has been demonstrated that 2D transition metal carbides can operate at rates exceeding those of conventional ELDCs, but can provide higher volumetric and areal capacitances than carbon.…”
Section: Mxenes Mofs and Compositesmentioning
confidence: 99%
“…Characterizations AJ EOL JSM-6700F scanning electron microscope (SEM) with an accelerating voltage of 5kVw as used to characterize the morphology of the samples, and aJ EOL2011m icroscope with an acceleration voltage of 200 kV was used to obtain EDX element mapping images. Transmission electron microscopy (TEM) analyses were per- rGO [2a] 12.4 1 pure MXene film [27] 288 1 900 N-Ti 2 CT x [3a] 327…”
Section: Preparation Of Co 3 O 4 -Mxene/rgo Hybrid Porous Aerogelsmentioning
confidence: 99%